Collaborative Digital Mashup Poetry Project: Exploring EFL Students’ Perceptions and Experiences - Yanti Sri Rezeki (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2025)
This study explores EFL pre-service teachers’ perceptions and practices of learning as the results of their collaborative digital mashup poetry project experience. Specifically, the study seeks to describe the nature of students’ mashup poetry projects, their collaboration strategies, and their perceived benefits and challenges of working on the multimodal project collaboratively. Involving 27 students in a Poetry in ELT class, data were generated from the results of group interviews, responses to online questionnaires, individual reflective notes, and samples of students’ work. The data were transcribed, coded, and categorized into relevant themes. The study revealed students’ positive perception regarding their collaborative project in terms of soft skill and digital literacy skill development. Concerns about ethical issues as well as technical difficulties were also found. This study suggests careful consideration for pedagogical implications on the use of collaborative digital poetry projects in the EFL higher education context.